Perception and knowledge : a phenomenological account - Hopp, Walter (New York: Cambridge university press, 2011)
This book argues that perceptual experiences do not have conceptual content, and that what makes them play such a distinctive epistemic role is something that sets them radically apart from beliefs.
1. Content; 2. Experiential conceptualism; 3. Conceptualism and knowledge; 4. Against experiential conceptualism; 5. Conceptual and nonconceptual content; 6. The contents of perception; 7. To the things themselves; Bibliography
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Perception (Philosophy).; epistemology